A comprehensive graphical modeling platform designed for integrated hydrological simulation. (October 2018) - Tian, Yong; Zheng, Yi; Han, Feng; Zheng, Chunmiao; Li, Xin
Abstract: This study developed a comprehensive graphical data processing and modeling system named Visual HEIFLOW (VHF) for integrated surface water-groundwater modeling. Its distinctive features include the following. First, VHF uses a generic multivariable-space-time data cube model, which enables the system to efficiently handle large time-series datasets over a large spatial domain. Second, VHF streamlines the entire modeling procedure from data preparation at the very beginning to visualization and analysis of modeling results in a uniform environment. Third, VHF allows updating the land use input at user-specified time points without manual intervention and therefore allows a direct simulation of the hydrological effects of changing land use. The applicability and versatility of VHF were demonstrated in a case study in the Heihe River Basin, the second largest inland river basin in China. The case study also demonstrated that VFH facilitates process understanding and supports management decision-making. Highlights: A multivariable-space-time data cube model to handle large spatiotemporal datasets. Procedure of integrated hydrological modeling streamlined in a uniform environment. Integrated hydrological modeling driven by time-variant land use data. Process understanding and management practices greatly facilitated by the tool.